2014
DOI: 10.1186/s12939-014-0087-1
|View full text |Cite
|
Sign up to set email alerts
|

Trends in and socio-demographic factors associated with caesarean section at a Tanzanian referral hospital, 2000 to 2013

Abstract: BackgroundCaesarean section (CS) can prevent maternal or fetal complications. Sub-Saharan Africa has the lowest CS levels in the world but large variations are seen between and within countries. The tertiary hospital, Kilimanjaro Christian Medical Centre (KCMC) in Tanzania has had a high level of CS over years. The aim of this study was to examine trends in the socio-demographic background of babies born at KCMC from year 2000 to 2013, and trends in the CS percentage, and to identify socio-demographic factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 37 publications
5
40
0
Order By: Relevance
“…The findings of this study are similar to those of the study conducted by Janoudi et al (2015) who discovered that women aged 35 or older experienced a greater number of obstetrical complications as compared to women aged between 20 and 34 with such complications putting them at risk of C/S. The findings of this study also concur with the study done by Nilsen (2014) which found that C/S in higher maternal age groups was associated with medical conditions such as hypertension and diabetes. Moreover, in the industrialised world, social, demographic and educational social trends combined with the greater accessibility of birth control and wider solutions to infertility problems has increased the proportion of women experiencing their first pregnancy after the age of 35 (Cohen, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings of this study are similar to those of the study conducted by Janoudi et al (2015) who discovered that women aged 35 or older experienced a greater number of obstetrical complications as compared to women aged between 20 and 34 with such complications putting them at risk of C/S. The findings of this study also concur with the study done by Nilsen (2014) which found that C/S in higher maternal age groups was associated with medical conditions such as hypertension and diabetes. Moreover, in the industrialised world, social, demographic and educational social trends combined with the greater accessibility of birth control and wider solutions to infertility problems has increased the proportion of women experiencing their first pregnancy after the age of 35 (Cohen, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Adolescent pregnancy is defined as pregnancy in a young girl between the age of 13 and19 (Spencer, 2011). According to Nilsen (2014), the high C/S percentages in adolescents could be caused by obstructed labour due to an immature birth canal. This means that they became pregnant before the pelvis had matured, resulting in cephalo-pelvic disproportion which plays a central role in obstructed labour.…”
Section: Discussionmentioning
confidence: 99%
“…High CS rates have been reported in other studies conducted in Tanzania25 29 (eg,31% at the Muhimbli Hospital and 35% in Kilimanjaro Christian Medical Center(KCMC)) probably because of the role played by a referral hospital in targeting high-risk pregnancies. This hypothesis could be confirmed by the higher CS rate in women referred from other facilities (63.7% in our study).…”
Section: Discussionmentioning
confidence: 87%
“…Nilsen et al 29 hypothesises that poor quality of care at the dispensary and HC level contributes to increasing the number of preventable CS in women who are referred late and in critical condition, meaning that by the time they get to the medical facility an emergency CS is the only possible action 31. In addition, several studies have highlighted the inadequacy of obstetric and neonatal care services at the primary level in Tanzania 32–34.…”
Section: Discussionmentioning
confidence: 99%
“…In low-resource countries, CS carries a greater risk to mothers when compared to high-resource countries due to numerous environmental and human resources factor implications such as potential for postpartum hemorrhage, wound infections, sepsis, injury to proximal organs, and death (Nilsen et al, 2014). A Tanzanian study found multiple adverse effects caused by CS, including high rates of maternal mortality, major medical impediment, and commonly death for the pregnant mother, at a similar rate to that from other major surgeries (Nilsen et al, 2014). Another adverse effect of CS identified in Tanzania is the high cost to the healthcare system, the woman, and her family (Kruk, Paczkowski, Mbaruku, de Pinho, & Galea, 2009).…”
Section: Id:p0120mentioning
confidence: 99%